2015
DOI: 10.1007/s00198-015-3326-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone architecture adaptations after spinal cord injury: impact of long-term vibration of a constrained lower limb

Abstract: Summary This study examined the effect of a controlled dose of vibration upon bone density and architecture in people with spinal cord injury (who eventually develop severe osteoporosis). Very sensitive computed tomography (CT) imaging revealed no effect of vibration after 12 months, but other doses of vibration may still be useful to test. Introduction The purposes of this report were to determine the effect of a controlled dose of vibratory mechanical input upon individual trabecular bone regions in people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
0
24
1
2
Order By: Relevance
“…For example, the most significant effect of the intervention in our study involved parameters related to microstructural connectivity —tibia stiffness and trabecular plate-to-rod ratio — which were not assessed in previous studies, except in Dudley-Javoroski et al (59). Furthermore, differences in DXA measures over the 6-month intervention were not discernable at spine or hip in our study.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the most significant effect of the intervention in our study involved parameters related to microstructural connectivity —tibia stiffness and trabecular plate-to-rod ratio — which were not assessed in previous studies, except in Dudley-Javoroski et al (59). Furthermore, differences in DXA measures over the 6-month intervention were not discernable at spine or hip in our study.…”
Section: Discussionmentioning
confidence: 86%
“…In the recent past, whole-body vibration (WBV) effects on bone architecture after SCI have been investigated with inconsistent results. In 2016, Dudley-Javoroski et al showed that 12 months of vibration training did not preserve BMD or trabecular architecture in subjects affected by chronic SCI, showing bone tissue insensitivity to mechanical loading interventions (63). These results are not in line with the previous studies performed on rats, where WBV seemed to attenuate the bone loss that commonly occurs during the early acute stages after SCI (64).…”
Section: Whole-body Vibrationmentioning
confidence: 92%
“…All subjects provided written informed consent before participating in the study. Participants were recruited from an ongoing study of vibration training as an anti-osteoporosis measure after SCI [8]. In brief, these participants received twice-weekly vibration training (30 Hz, 0.6 g ) to one lower limb while seated in a wheelchair.…”
Section: Methodsmentioning
confidence: 99%
“…The loss of this pervasive source of load may play an important role in the precipitous decline of bone integrity experienced by patients with SCI [1]. Studies that reintroduce vibration as an antiosteoporosis countermeasure are underway [8, 17]. Vibration is also being investigated as a method to reduce spasticity [2, 14], one of the most prevalent and bothersome secondary heath conditions of SCI [6].…”
Section: Introductionmentioning
confidence: 99%